Bioreducible poly(2-ethyl-2-oxazoline)–PLA–PEI-SS triblock copolymer micelles for co-delivery of DNA minicircles and Doxorubicin - Gaspar, Vítor Manuel Abreu (2018)
The co-delivery of minicircle DNA (mcDNA) and small anti-cancer drugs via stimuli-sensitive nanocarriers is a promising approach for combinatorial cancer therapy. However, the simultaneous loading of drugs and DNA in nanosized delivery systems is remarkably challenging. In this study we describe the synthesis of triblock copolymer micelles based on poly(2-ethyl-2-oxazoline)–poly(L-lactide) grafted with bioreducible polyethylenimine (PEOz–PLA-g–PEI-SS) for co-delivery of supercoiled (sc) mcDNA vectors and Doxorubicin (Dox). These amphiphilic carriers take advantage of non-fouling oxazolines to confer biological stability, of PLA to provide a hydrophobic core for drug encapsulation and of bioreducible PEI-SS to provide mcDNA complexation and an on-demand stimuli-responsive release. The obtained results show that mcDNA-loaded micelleplexes penetrate into in vitro tumor spheroid models with specific kinetics and exhibit a higher gene expression when compared to non-bioreducible nanocarriers. Moreover, in vivo bioluminescence imaging showed that gene expression is detected up to 8 days following mcDNA-micelles intratumoral administration. Furthermore, drug–gene co-delivery in PEOz–PLA-g–PEI-SS carriers was verified by successful encapsulation of both Dox and mcDNA with high efficacy. Moreover, dual-loaded micelleplexes presented significant uptake and a cytotoxic effect in 2D cultures of cancer cells. The co-delivery of mcDNA-Dox to B16F10-Luciferase tumor bearing mice resulted in a reduction in tumor volume and cancer cells viability. Overall, such findings indicate that bioreducible triblock micelles are efficient for focal delivery in vivo and have potential for future application in combinatorial DNA-drug therapy.